Psychiatric nurses’ experiences of using a model to improve relationships of couples with borderline personality disorder - Andile G. Mokoena-de Beer; Annie Temane; Nompumelelo Ntshingila (South African Journal of Psychiatry)
Background: Individuals with borderline personality disorder (BPD) struggle with relationships because of impulsivity and emotional regulation difficulties. Specialised skills are needed for care, but existing models are lacking. A new model was developed to help psychiatric nurses support couples with one partner having BPD. This innovative psychiatric nursing model emphasises the need for implementation and evaluation in care.